Estudo das patologias em edificações da Universidade Federal Rural do Semi-Árido campus Mossoró-RN - Alves, Davi Wesley Moreira (Universidade Federal Rural do Semi-Árido, 2018)
The Engineering works started using advanced technological resources not only in the use of materials, but also in constructive techniques. However, pathological problems are present in small, medium or large works. Aiming at conducting a study of the main pathological manifestations found in the buildings of the Federal Rural Semi-Arid University, in the city of Mossoró-RN, this paper presents a brief description of the most recurrent pathological manifestations together with concepts used in the study of constructive pathologies, followed by a quality control approach inserted in the stages of the constructive process. Pathological manifestations are explored in civil engineering works, raising hypotheses that can justify the possible causes being found in this study cases like cracks, cracks, cracks, corrosion of reinforcement, plaque detachment, infiltration, blemishes and mold. Finally, we highlight the importance of quality control and an inspection program as a way to soften or eradicate some pathological problems that may lead to cases of anomalies explored here.
Monografia
Keywords: Construção civil; Estrutura; Controle de qualidade; Civil construction; Quality control; Structure; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA